PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP PERALIHAN MEREK DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI - Romindo Pasaribu (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2019)
ABSTRACT OPPO smartphone is a product that comes from China. So far, Indonesian people have been flooded with smartphones with the SAMSUNG brand, but the SAMSUNG brand started from its market in Indonesia after OPPO entered the Indonesian market. Hypotheses in the study consisted of: (1) H1: There is an influence of Electronic Word of Mouth on brand transition, (2) H2: Related to Electronic Word of Mouth on brand image, (3) H3: related to the search image of brand transition, and (4) H4: Related to the influence of Electronic Word Of Mouth on brand image and brand transition. The nature of this research is explanatory research. The research location is in the city of Medan. When the study will be conducted from March to August 2019. The number of respondents in this study were 100 people. The results of the study are as follows: (1) Electronic word of mouth stated positive and not significant to brand transfer. After further testing, namely to study directly and indirectly each of these variables, the results obtained indicate that E-WOM is not directly related to the OPPO smartphone brand in Medan. (2) Electronic word-of-mouth has a positive and significant effect on the transfer of the OPPO smartphone brand in the city of Medan. The significance value in testing this variable shows positive and significant results. (3) The image of a positive and significant recommendation for the placement of the OPPO smartphone in the city of Medan. Brand image is one very important factor for customers who can win a product. (4) Electronic word of mouth has a positive and significant influence on brand relationships with brand image as a contributing variable.